2015
DOI: 10.1007/s12094-015-1372-1
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of circulating tumor cells in metastatic breast cancer: a systemic review and meta-analysis

Abstract: Based on these results, we propose that HER2 positivity could be a significant risk factor for the presence of CTCs. Additionally, CTCs have a significant prognostic value for MBC patients. Therefore, CTCs should be continually monitored to guide the treatment of MBC patients, especially those with HER2 + primary tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(33 citation statements)
references
References 39 publications
0
32
0
Order By: Relevance
“…Clinical endpoints were PFS and OS. PFS and OS were calculated from the time of the first draw for CTCs or ctDNA until the progression (assessed using RECIST criteria) or death, respectively (22,23,(28)(29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical endpoints were PFS and OS. PFS and OS were calculated from the time of the first draw for CTCs or ctDNA until the progression (assessed using RECIST criteria) or death, respectively (22,23,(28)(29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%
“…The meta-regression analysis results showed that clinical tumor stage was the main source of heterogeneity. When these 11 studies were omitted, the heterogeneity was reduced, strongly establishing that patients with MBC should be analyzed separately to achieve additional optimal results5758.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a CTC count ≥ 5 indicated a worse treatment response in MBC patients [84]. The prognostic value of CTC enumeration has been demonstrated in abundant types of tumors, such as those in prostate cancer, lung cancer, pancreatic cancer and colorectal cancer, via large clinical trials and pooled analyses [85-89].…”
Section: Diagnosis and Prognosis Assessmentmentioning
confidence: 99%